Urban Streamflow Impact Assessment (USIA): a novel approach for protecting urbanising waterways and providing the justification for integrated water management. Issue 2 (3rd July 2021) - Kermode, Stephanie; Vietz, Geoff; Tippler, Carl; Russell, Kathryn; Fletcher, Tim; van der Sterran, Marlène; Birtles, Phillip; Dean, Michael
ABSTRACT: As urban populations expand globally, the associated increase in urban land cover directly impacts the social and environmental amenity of natural assets, including waterways. The primary driver of urban waterway degradation changes in land uses which results in altered hydrology – from stormwater runoff, and where present, wastewater treatment plant discharge. Whilst the impacts of pollutants are relatively well regulated via public policy, a gap remains for the management of flow regime modification. The Urban Streamflow Impact Assessment (USIA) was developed to fill this management and planning knowledge gap. The approach begins with the identification of waterway values (social, ecological and geomorphic) then explicitly links these values to streamflow characteristics using hydraulic and hydrologic metrics. USIA was applied to a case study in Western Sydney and demonstrated the loss of values associated with 'business-as-usual' approaches to stormwater and wastewater management. Conventional stormwater management approaches do not remove enough excess flow to meet reasonable outcomes for the waterway. This excess runoff is increasingly seen as a resource and opportunity for improving water security and liveability. USIA is consistent with regulatory frameworks and can be applied across developing and established urban catchments to provide explicit input to planning controls. The approach is appropriate at multiple scales, informing urban planning from a broad strategic level through to detailed design. By linking social and ecological values with geomorphic and flow requirements, the approach enables an understanding of which management approaches could allow desirable waterway outcomes to be met.